Psychological Well-Being and Body Image among the Students of the Hashemite University in Jordan - Alkhazaleh, Ziad M.; Mhaidat, Fatin A.; Alharbi, Bassam H. (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed at identifying the relationship between the psychological well-being and the negative body image among the students of the Hashemite University. on a sample comprising (726) students. The researchers used two study tools: Psychological well-being and the negative body image. The results of the study concluded that there was a negative correlation between the psychological well- being and the negative body image. It found that the higher the level of the psychological well-being the less the negative body image. Through the use of the Multiple Regression Analysis, the study results concluded that there were three dimensions of psychological well-being, that could predict the body negative image; positive relations with others, personal growth and purpose in life.